Procurement of Category 2 Vaccines in China - Jian-Lin Zhuang; Abram L. Wagner; Megan Laffoon; Yi-Han Lu; Qing-Wu Jiang (Vaccines, 2019)
Internationally, vaccine pricing is relatively opaque, although many low- or lower-middle-income countries belong to international consortiums that jointly procure vaccines. China procures vaccines domestically, and vaccines that require payment from the public (“category 2 vaccines”), have undergone several regulatory changes over the past 15 years. This study aims to describe the vaccine procurement method changes in China since 2005 and to analyze how the procurement method impacted vaccine price. This review of vaccine procurement reforms found that a shift to provincial-level Group Purchasing Organizations after 2016 was accompanied by an increase in most prices. There was more variability in vaccine prices across provinces for vaccines with only one supplier, and these vaccines have a higher price than what is found in United Nations Children’s Fund (UNICEF)-supported countries. China’s current procurement system for non-mandatory vaccines leaves these vaccines costing several-fold more than in other countries, and in particular those supported by Gavi, the Vaccine Alliance. Exploring a variety of methods to reduce vaccine purchase prices will not only directly benefit the general population, but also the government, as they aim to implement more programs to benefit public health in a cost-effective manner.